Customer perspective on overbooking: The failure of customers to enjoy their reserved services, accidental or intended?. (June 2016) - Guo, Xiaolong; Dong, Yufeng; Ling, Liuyi
Abstract: Overbooking is widely applied in the service industry to hedge against undesirable situations, such as cancellations and no-shows. However, during the implementation of overbooking, service providers may turn down some customers when the number of arrivals exceeds their capacity on the target date. Therefore, this paper examines overbooking from the customers' perspective to offer them a clear perception on the possibility for their reservations to be denied by the service provider. By establishing a Stackelberg model between a service provider and an online travel agency, we explore how optimal overbooking strategy is developed by the service provider. Afterward, by analyzing the obtained optimal overbooking pad, we calculate the probabilities of denied service under different levels of monetary compensation that is paid to denied customers. A higher monetary compensation guarantees a higher chance of successful service. This paper also provides customers with some reference when booking services. Highlights: Give analysis about overbooking strategy from the customers' perspective. Analyze the denied probability with successful reservations. Help the customers estimate the denied possibility according to the denied compensation. The service providers are recommended to announce the value of denied compensation.